Frauen und Geschlechter Bilder - Rollen - Realitäten in den Texten antiker Autoren zwischen Antike und Mittelalter - Rollinger, Robert (2006)
This volume is an outcome of the FWF project P14853 "Ethnographie - Gender-Perspektive - Antikerezeption". The research project intended to connect ancient ethnography, gender studies and the running methodological debate. For this purpose the collaborators to the project organised two workshops. The volume contains the revised papers held at the first workshop Frauenbild und Geschlechterrollen bei antiken Autoren der römischen Kaiserzeit at the University of Innsbruck, 5.-8. 3. 2003. According to the goal of this workshop the papers connect the theoretical debates of postmodernism und feminism with the daily work of historians or philologists. Each paper touches , in some way or other, the premise underlying the mentioned project that an author's profile can be uncovered by comparing his text with other texts synchronically and diachronically. Most of the papers deal with the Roman imperial period. As a whole they cover the time span from the 5th century BCE to the 6th century CE. But they are not arranged chronologically but systematically. First comes a methodological introduction (C. Ulf and K. Schnegg) connected with a description of the papers. The first section then contains five articles pointing at the 'basis and kind of text and its lecture' (Grundlagen und Formen der Texte und der Textlektüre). The authors deal with Augustine, archaeological remains, and modern movies as well. Seven articles focusing on the topic 'historical realities within texts' (Historische Realität(en) im Text) build up the second section. They deal with the attic democray, Augustean propaganda, and authors from Cornelius Nepus to Synesios of Cyrene. In the last section 'text levels and pictures of sexes' (Textebenen und Bilder der Geschlechter) the reader finds articles concerning some aspects of ancient ethnography and the gender perspective of authors from Tacitus to Ennodius. The volume offers, in a broad chronological spectrum, varied perspectives on and ways of dealing with texts by separating consciously the search for historical realities form the interpretation of texts.